A new active resistor and its application to a CMOS transconductor. (November 2018) - Rezaei, Farzan
Abstract: In this paper a new active resistor is proposed which is suitable for tunable linear voltage to current converters. The proposed resistor is composed of the main and auxiliary triode-mode transistors in which the resistance of auxiliary transistor adds to that of main transistor at a specific tune voltage. By this way the triode operation of both transistors is ensured throughout the tuning range. The proposed resistor is used in a tunable linear transconductor. The proposed transconductor which is implemented in 0.13 μm CMOS technology works with 1.2 V supply voltage and its power consumption changes between 682 and 980 μW. Simulation results show 20 dB improvement in THD of transconductor thanks to using proposed resistor rather than conventional one for input voltage amplitude of 1Vpp at 1 MHz. The transconductance can be tuned from 68 to 177.4 μA/V and the THD remains less than −55 dB for input voltage amplitudes up to 1.2Vpp and for the entire tuning range.